Characteristics, management, and major adverse cardiac events of ST-elevation myocardial infarction (STEMI) patients in rural area: a Jember acute coronary syndrome medical records study - Calista Padma Paramitha Sugiyanto; Suryono; Ayu Munawaroh (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
The mortality and morbidity of ST-elevation myocardial infarction (STEMI) remain high, and it is still the leading cause of death worldwide. Timely reperfusion lowers the risk of MACE and improves survival. However, reperfusion delay is still a significant issue in developing countries, particularly rural area. This study aimed to determine the characteristics, management, and major adverse cardiac events of STEMI patients in Jember Distric to enhance reperfusion therapy in rural areas. It was an analytical observational cross-sectional study with a quantitative method. A total of 108 medical records of STEMI patients of the Dr. Soebandi District Hospital, Jember in period of 2019 to 2020 were included using the consecutive sampling technique. As much as 78 (62%) of the patients did not receive reperfusion therapy while the remaining patients (41 or 38%) received the therapy, namely percutaneous coronary intervention (20 or 18.5%), fibrinolytic therapy (19 or 17.6%), and both (2 or 1.9%). Multivariate analysis for reperfusion was statistically significant (p=0.016; OR 3.688 95% CI: 1.274-10.679). The level of education, health funding, and distance to the hospital did not affect the delay of the reperfusion therapy. Reperfusion was highly associated with the incidence of MACE and this study discovered a threefold benefit of reperfusion in lowering the occurrence of MACE (p=0.016). In conclusion, the majority of STEMI patients does not get reperfusion therapy. Delays in reperfusion treatment are not related to the patient's level of education, health funding, or distance to the hospital. Nonetheless, the delay my be attributed to the Jember community's lack of awareness of STEMI symptoms.